INOKULASI BIONODULIN DAN PUPUK KOTORAN SAPI TERHADAP KARAKTERISTIK FISIOLOGIS, KOMPONEN HASIL DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) PADA ULTISOLS - Rahni, Nini Mila (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2013)
The objective of this study was to increase growth and yield of peanut on Ultisols series by inoculation of bionodulin and cow manure. The field experiment was carried out at the Kendari, South-East Sulawesi. The experiment was arranged Randomized Block Design in a factorial with three replications. The first factor were inoculation of bionodulin (0,1, 2 and 3) g 150 g-1seeds and the second factor was manure (0, 5, 10 and 15) ton ha-1. The result showed that inoculation of bionodulin and application manure had significant on LAI, CGR, NAR and RSS of plant. Bionodulin and manure application until certain level, increased yield components and yield. The inoculation of 1 g 150 g-1 seeds biofertilozer and application 15 ton ha-1 manure gave a maximum yield of 5,26 ton ha-1.